The Impact of Cigarette Excise Tax Policy on Tobacco Market and Clove Market in Indonesia - Suprihanti, Antik; Harianto, Harianto; Sinaga, Bonar M.; Kustiari, Reni (International Journal of Economics and Financial Issues, 2018)
Indonesian government has applied tariff tax policy on cigarette that caused consequences not only to cigarette market but also to cigarettes input mainly tobacco and clove. The aim of this research was to analyze the impact of the rise of cigarette excise tax on tobacco market and clove market in Indonesia. This research used the data series of 1990-2016 with simultaneous equation system and estimated using 2SLS (Two-Staged Least Squares) method. The results show that the rise of the excise tax decreased the production slightly of all kretek cigarettes production. It impact on the decrease on tobacco and clove consumption of clove cigarette industries by 0.06 percent and 0.05 percent, respectively. Nevertheless, demand of tobacco and clove still rose even in small number and increased the supply of tobacco but not on clove. Whereas, the price of these commodities precisely declined in farmer's level which indicated that there were a gap caused by oligopoly market structure of cigarette industries. It showed that there were dependence of farmer on cigarette industries. Cooperation between farmers and cigarette industries and supporting government regulation were needed. The research and development are needed through diversification of tobacco plant and developing clove products to minimize the dependency. Keywords: cigarette excise tax policy, tobacco, clove. JEL Classification: H2 DOI: https://doi.org/10.32479/ijefi.7228